ANALYSIS OF THE ALGORITHM FOR DETERMINING CATTLE CASCADE - Xaniyev N.M (Web of Journals Publishing, 2025)
Currently, special attention is paid to automation processes in all industries. One of the pressing problems in the veterinary sector is also the automation of the activities of specialists. This article considers the issue of controlling information flows based on an algorithm for detecting errors in the detection of animal diseases. The study proposes a method for the detection of complex diseases based on analytical indicators. This allows veterinarians to detect the disease early.
Keywords: Animal diseases, early detection of the disease, method of integrated analysis based on analytical values, automation, artificial testing, evaluation by criteria.